Development of A Transient Recorder for Lightning Impulse Voltage Measurement - Chaisiri, Punyavee; Pramualsingha, Sarawuth; Yutthagowith, Peerawut (My University, 2024)
This paper presents the development of a transient recorder specifically designed for the measurement of lightning impulse voltage (LIV), primarily used for high-voltage insulation testing purposes. The developed transient recorder comprises a passive attenuator, a 12-bit digital oscilloscope, and a full LIV parameters evaluation software. The software, implemented using Python 3.11, utilizes Levenberg-Marquardt nonlinear regression for the determination of base curve coefficients, conforming to the IEC 60060-1:2010 standard methodology. LIV parameters, including peak voltage, front time, time to half, and overshoot rate, determined by the software, meet the accuracy requirements of IEC 61083-2:2013. Validation involved testing with 29 standard LIV waveforms generated by a test waveform generator (TDG). Additionally, LIV generated by LIV calibrator (KAL 1000 DR. STRAUSS) was used to confirm the proper functioning of the developed transient recorder. The developed transient recorder was also deployed with a capacitive voltage divider for testing commercial transformers in a manufacturing facility, where it performed effectively. This achievement should encourage the adoption of this measuring system in every high-voltage laboratory, promoting domestic production over imports.